Passage of I(131)-albumin and I(125)-gamma globulin into the small intestine of the pig - Dich, John (1964)
Metabolism of I(131)-albumin and I(125)-gamma globulin was examined simultaneously in 5 pigs (22-30 kg. bodyweight). Total daily catabolism of albumin and gamma globulin was 12-23 per cent/day and 10-13 per cent/day rsp. The excretion of the two proteins into the small intestine was studied in Thiry-Vella type loops, situated at different levels of the small intestine. Considerable amounts of protein-bound radio-activity could be detected in succus entericus. Perfusions with isotonic magnesium sulphate solution, normal saline and 10 per cent magnesium sulphate solution were followed by increased excretion of both proteins. The increase was very considerable, even when isotonic fluids were used. The excretion of the two proteins was of the same order of magnitude. Quantitative aspects are discussed with special reference to the difficulties derived from the fact that little is known on secretory variations along the intestine and on the role played by the passage of digesta in the excretion of proteins.